Student Concept Understanding Analysis In Number Pattern Material During Distance Learning (DL): Analisis Pemahaman Konsep Siswa Dalam Materi Pola Bilangan Selama Pembelajaran Jarak Jauh (PJJ) - Novita, Nita; Sumarni, Sumarni; Riyadi, Mohamad (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2022)
The background of this research is that students still do not understand the concept of determining number patterns, especially during Distance Learning (DL). The purpose of this study was to determine the students' conceptual understanding ability and to find out how teachers teach number pattern material during DL. This research is a qualitative descriptive research. This research was carried out at MTs Pertiwi Kuningan for the academic year 2020/2021 in class VIII A as many as 16 students and a mathematics teacher. The data sources for this research are the results of written tests and interviews. Based on the results of data analysis, it shows that the ability to understand mathematical concepts of students in the high category is 45%, the medium category is 40% and the low category is 15%. The results of this study also showed that the students' abilities from each indicator were as follows: 1) students in the high category were able to do all the questions correctly, 2) students in the medium category were able to work on 6 items or mastered 6 indicators of conceptual understanding ability; 3) students with low indicators can work on 4 questions or master 4 indicators of concept understanding ability.